Application of arbitrary and individualized load quantification strategies over the weekly microcycle in professional soccer players - Padrón-Cabo, A.; Solleiro-Duran, D.; Lorenzo-Martínez, M.; Nakamura, F. Y.; Campos-Vázquez, M.; Rey, E. (Biology of Sport, 2024)
The aims of this study were to: (a) determine the differences in external load quantification between arbitrary and individual speed thresholds over the weekly microcycle in professional soccer players, and (b) analyse the association between internal load and different external load quantification strategies (ELQSs). Ten professional outfield players were monitored during training sessions and official matches using 10 Hz GPS devices over a 6-week in-season period. The absolute and relative ("R" before the distance category) distances covered were calculated for the following external load variables: medium-intensity running distance (MIR), high-intensity running (HIR), sprint distance (SD), and very high-intensity running (VHIR). Individualized thresholds were determined based on maximal sprinting speed (MSS) and the last speed achieved during the 30-15 Intermittent Fitness Test (VIFT) of each player. In terms of match-day workload, significant differences (p < 0.05) were observed between arbitrary and individualized strategies (i.e., MSS and VIFT) for the distance covered in MIR, HIR, SD, VHIR, RHIR, RSD, and RVHIR. The MSS strategy compared to arbitrary thresholds revealed significant differences (p < 0.05) for distance covered in HIR, RHIR, and VHIR during all training sessions. The present results showed that arbitrary thresholds lead to underestimation of external load absolute and relative metrics compared to the MSS strategy throughout the microcycle. The VIFT strategy mainly revealed differences in external load quantification regarding MD compared to arbitrary thresholds. Individualized speed threshold strategies did not achieve better associations with internal load measures in comparison with arbitrary thresholds in professional soccer players.